2014
DOI: 10.1016/j.ijhydene.2014.01.150
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Ni/SiO2 catalyst preparation methods on hydrogen production from the pyrolysis/reforming of refuse derived fuel

Abstract: Hydrogen production from the pyrolysis/reforming of refuse derived fuel (RDF) was investigated with a series of Ni/SiO 2 catalysts. The catalysts were prepared by homogeneous precipitation derived from a sol-gel method (HPG) and compared to Ni/SiO 2 catalysts prepared by adding a phase separation step to the HPG process (B-HPG). All the catalysts had a NiO loading of 10 wt.%, and three different calcination temperatures (500 ºC, 700 ºC and 900 ºC) were used for each method. The prepared Ni/SiO 2 catalysts were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 35 publications
1
10
0
Order By: Relevance
“…From Table 1, Ni/SiO2 catalyst have a higher surface area than Cu/SiO2 which may be caused by the optimum calcination temperature of Ni catalyst. As reported by Blanco et al (2012), calcination temperature at 500-550°C is optimum condition for calcined and reduced Ni 2+ become Ni°deposited on SiO2 [12]. This data is supported by XRD analysis showed the sharp diffraction of Ni metal.…”
Section: Characterization Of Ni/sio2 and Cu/sio2supporting
confidence: 75%
See 2 more Smart Citations
“…From Table 1, Ni/SiO2 catalyst have a higher surface area than Cu/SiO2 which may be caused by the optimum calcination temperature of Ni catalyst. As reported by Blanco et al (2012), calcination temperature at 500-550°C is optimum condition for calcined and reduced Ni 2+ become Ni°deposited on SiO2 [12]. This data is supported by XRD analysis showed the sharp diffraction of Ni metal.…”
Section: Characterization Of Ni/sio2 and Cu/sio2supporting
confidence: 75%
“…The large hump (broad peak) at around 22-30° (Fig. 1b) showed the low degree crystallinity of SiO2 by the formation of physical interaction between silica and metal [12][13]. Changing the crystallinity of SiO2 to amorphous after deposition of the metal increased the acidic surface of the catalyst and then enhance the catalytic activity [14].…”
Section: Characterization Of Ni/sio2 and Cu/sio2mentioning
confidence: 98%
See 1 more Smart Citation
“…Figure shown the adsorption‐desorption isotherm curves of N 2 at 77 K to measure the surface area for pure Al 2 O 3 and metal‐modified Al 2 O 3 , and their textural properties were summarized in Table . Based on IUPAC classification, all the isotherms were found to be type IV, and the H1 hysteresis loops related to mesoporous materials with wide pore size distribution were also observed for all samples . According to the results of characterization, we can concluded that there were no significant difference in the uptake of nitrogen (N 2 ) at relative pressure (P/Po) range of 0.1‐0.9.…”
Section: Resultsmentioning
confidence: 91%
“…Methyl mercaptan (CH 3 SH) is an organic sulfur compound, which inevitable existed and emitted from many industry processes, such as, paper making, leather making, pulping, glue making, fur production, oil and gas exploitation, wood‐pulping and some others pollution activities . At the same time, CH 3 SH presented high toxicity to human and environment .…”
Section: Introductionmentioning
confidence: 99%